2015
DOI: 10.17511/ijmrr.2015.i2.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Platelet count and C-Reactive Protein among Gram Positive, Gram Negative and Fungal Sepsis in Newborns

Abstract: Introduction: Septicemia is characterized by positive blood culture, thrombocytopenia & elevated C-reactive protein. Objective: To compare platelet indices and CRP among gram-positive, gram negative and fungal sepsis in newborns. Methods: This is a retrospective case analysis of 52 blood culture positive patients between January-2012 to December-2014. The parameters examined were Baseline Platelet Count, Change In Platelet Count, (Baseline Platelet count-Change in Platelet count)/ Baseline Platelet Count , Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Similarly, while comparing hematological, infectious, and blood complete counts, it was discovered that in the case of C-reactive protein, the greater the CRP level, the lower the platelet level. This finding was also supported by Rabindran et al, in which they studied the CRP with platelet level in neonates and found out that the greater the CRP, the higher the thrombocytopenia [ 25 ]. Furthermore, the severity of gram-negative sepsis increased.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, while comparing hematological, infectious, and blood complete counts, it was discovered that in the case of C-reactive protein, the greater the CRP level, the lower the platelet level. This finding was also supported by Rabindran et al, in which they studied the CRP with platelet level in neonates and found out that the greater the CRP, the higher the thrombocytopenia [ 25 ]. Furthermore, the severity of gram-negative sepsis increased.…”
Section: Discussionsupporting
confidence: 65%
“…Rabindran et al also found that risk of fungal sepsis was significantly higher in lower birth weight babies as compared to bacterial sepsis (p value = 0.014). 10 In the present study, majority of the maternal factors were found insignificant like meconium stained liquor (MSL), per vaginal examinations >3 and maternal fever and mode of delivery. Similar result for mode of delivery was found by Ho Lim W et al, Chib R et al 12,9 There were some studies on risk factors for fungal sepsis which showed insignificance of mode of delivery like Chaurasia D et al and Yunus M et al 24,11 On the other hand, Swanson JR et al found caesarean section as a significant risk factor for Candidial sepsis (p value <0.0001).…”
Section: Discussionmentioning
confidence: 46%
“…Corroborating with the present findings, Rabindran et al found higher incidence of reactive CRP (p value = 0.003) in fungal sepsis as compared to bacterial sepsis. 10 Study by Ho Lim W et al also showed similar result (100% versus 83.5%, p value = 0.009). 12 In systemic fungal infections, CRP levels are high as compared to superficial fungal infections like acute fungal stomatitis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations